Two Concepts of God - Lachs, John (Harvard theological review, 1966)
Philosophers have long debated the question of the existence of God. This is one of many philosophical issues in which the motivation for inquiry has come more perhaps from the side of human feeling than from disinterested scientific curiosity. Powerful emotions appear to prompt thinkers to devote effort to the attempt to prove or disprove the existence of God. The urgency of this task has made some of these philosophers pay less than adequate heed to the concepts they employ. It appears to have escaped the attention of many of them that the word “God” does not have a single meaning either in religious language generally or in philosophical theology. It is obvious that one of the important ways in which religious traditions differ is in their conceptions of the Deity. But a considerable number of different God-concepts may be distinguished in the Judeo-Christian religious tradition itself, and not even in Christian theology proper is the word “God” free of ambiguity.